Conceptual design models for social values of urban forests [in Sundsvall] - Mojtabaei, Sharareh (2021)
There is an ongoing urban development process in Sundsvall and the proper provision of the social values of urban forests that can meet public needs is now one of the issues for the municipality to deal with in planning. Moreover, the recent focus on the rehabilitative aspects of forests in human health has become a strong motivation for the municipality to invest in providing sufficient and proper networks of greenery over the city. Therefore, to provide such values for establishing a sustainable connection between nature and urban life, studying the social values of urban forests and the municipality’s objectives is considered essential.